Exploring global research trends in Chinese medicine for atherosclerosis: a bibliometric study 2012–2023 - Tan, Moye; Wang, Jiuyuan; Chen, Zhengxin; Xie, Xuejiao (Frontiers in Cardiovascular Medicine, 2024)
Background While Traditional Chinese Medicine (TCM) boasts an extensive historical lineage and abundant clinical expertise in addressing atherosclerosis, this field is yet to be penetrated adequately by bibliometric studies. This study is envisaged to evaluate the contemporary scenario of TCM in conjunction with atherosclerosis over the preceding decade while also identifying forthcoming research trends and emerging topics via the lens of bibliometric analysis. Methods Literature pertaining to TCM and atherosclerosis, circulated between January 1, 2012 and November 14, 2023, was garnered for the purpose of this research. The examination embraced annual publications, primary countries/regions, engaged institutions and authors, scholarly journals, references, and keywords, utilizing analytical tools like Bibliometrix, CiteSpace, ScimagoGraphica, and VOSviewer present in the R package. Result This field boasts a total of 1,623 scholarly articles, the majority of which have been contributed by China in this field, with significant contributions stemming from the China Academy of Traditional Chinese Medicine and the Beijing University of Traditional Chinese Medicine. Moreover, this field has received financial support from both the National Natural Science Foundation of China and the National Key Basic Research Development Program. Wang Yong tops the list in terms of publication count, while Xu Hao's articles take the lead for the total number of citations, positioning them at the core of the authors’ collaborative network. The Journal of Ethnopharmacology leads with the most publications and boasts the greatest total number of citations. Principal research foci within the intersection of Chinese Medicine and Atherosclerosis encompass disease characteristics and pathogenic mechanisms, theoretical underpinnings and syndrome-specific treatments in Chinese medicine, potentialities of herbal interventions, and modulation exerted by Chinese medicines on gut microbiota. Conclusion This analysis offers a sweeping survey of the contemporary condition, principal foci, and progressive trends in worldwide research related to Traditional Chinese Medicine (TCM) and atherosclerosis. It further delves into an in-depth dissection of prominent countries, research institutions, and scholars that have made noteworthy strides in this discipline. Additionally, the report analyzes the most cited articles, research developments, and hotspots in the field, providing a reference for future research directions for clinical researchers and practitioners.